(3aj adSaI GdMces (3fU aj Mce GdCeQGA GdbOjS JheG GdCchjfjs - (3YQaI, cQe YHGSs; (3Mfaj, MSfs ((3GdbGgQIs (3GdecJHIs, 2009)
(3Ef fU (B"(3aj Mce GdCeQGA(B" (3VQhQj ddJYQa Ydi GdacQ GdSjGSj ddbOjS JheG GdCchjfj, QeR GdcGKhdjcjI, heDSS GddGghJ GdeSjMj Ydi GdYbd hdG SjeG Cfg GdfU GdhMjO GdNGdU aj GdSjGSI dJheG GdCchjfj hdcf dG jfHZj GdGYJeGO Ydjg hMOg aj GdJYQa Ydi eLed GdBQGA GdSjGSjI ddbOjS, adGHO Cf jhVY aj SjGb ZjQg ef GdfUhU, HEVGaI dSjGb YUQ GdCchjfj faSg, aVdkG Yf QHWI HGSJeQGQ eY GdSjGSI GdCQSWjI hGdJj JYJHQ GdCSGS GdPj Yhd Ydjg GdCchjfj dJTjjO fSbg GdSjGSi, adbO MGhd GdJhajb Hjf GdadSaI GdSjGSjI GdCQSWjI hGddGghJ GdeSjMj, hcGfJ eMGhdJg Jdc CjSQ HWHjYI GdMGd ef eMGhdJg GdJhajb Hjf ejJGajRjbG CQSWh hGdOjf GdeSjMj(B. (3hYdi GdQZe ef Cfg jecf GYJHGQ GdadSaI GdSjGSjI GdCQSWjI GdCSGS GdPj GYJeO Ydjg GdCchjfj aj HfGA fSbg GdSjGSj EdG Cfg de jcf ebdOkG hdG JGHYkG dCQSWhs
12
Keywords: (3fXe GdMces